ANALYSIS OF CAPITAL, ASSET QUALITY, PROFITABILITY AND LIQUIDITY TOWARDS PROFITABILITY IN BANKING COMPANIES IN INDONESIA STOCK EXCHANGE - Rizky Novia Darma; Aloisius Hama (Institute of Computer Science (IOCS), 2022)
Commercial banks are banks that play an important role in advancing the nation through the products provided, and banks are a source of income for the state. For this reason, it is very important to know the management performance of Indonesian commercial banks listed on the Indonesia Stock Exchange through their profitability growth, this underlies the researcher using conventional commercial banks listed on the Indonesia Stock Exchange (IDX) as the object of research. Based on this description, this study aims to determine the effect of capital, asset quality, profitability and liquidity on profitability at conventional commercial banks listed on the Indonesia Stock Exchange. The population in this study are Conventional Commercial Banks listed on the Indonesia Stock Exchange (IDX). Banks that meet the requirements as a sample in this study are 40 banks. Then multiplied by 3 years period, starting from 2017–2019. So, the total number of observations (40 x 3) is 120 data units in this study. Regression analysis is basically a study of the dependence of the dependent variable with one or more independent variables. Based on the results of multiple linear regression, it can be seen that leverage has no effect on tax avoidance. This shows that companies that have high or low leverage ratio values ??during the first, second, and third quarters of 2020 do not affect the company's decision to take tax avoidance actions. Based on the results of multiple linear regression, it can be seen that company size has no effect on tax avoidance. The results show that both companies that have large and small asset values ??during the first, second, and third quarters of 2020 do not influence the company's decision to take tax avoidance actions.